Peripheral inflammation related to lower fMRI activation during a working memory task and resting functional connectivity among older adults: a preliminary study. (19th April 2016) - Dev, Sheena I.; Moore, Raeanne C.; Soontornniyomkij, Benchawanna; Achim, Cristian L.; Jeste, Dilip V.; Eyler, Lisa T.
Abstract : Objective: Peripheral inflammation has been associated with adverse effects on cognition and brain structure in late life, a process called 'inflammaging.' Identifying biomarkers of preclinical cognitive decline is critical in the development of preventative therapies, and peripheral inflammation may be able to serve as an indicator of cognitive decline. However, little is known regarding the relationship between peripheral inflammation and brain structure and function among older adults. Methods: Twenty−four older adults (mean age = 78) underwent a functional magnetic resonance imaging (fMRI) resting state functional connectivity scan, and a subset (n = 14) completed the n‐Back working memory task in the scanner. All participants completed a blood draw, and inflammation was measured with interleukin 6 (IL‐6) and C‐Reactive Protein (CRP). Results: Surprisingly, age was unrelated to measures of inflammation (IL‐6, CRP) or brain function (default mode network (DMN) connectivity; working memory performance; blood oxygenation level dependent (BOLD) activation with higher working memory load). However, lower functional connectivity between the left parietal seed and all other DMN regions was associated with higher levels of IL‐6 and CRP. Additionally, greater plasma concentration of IL‐6 was associated with lower BOLD activation in the left middle frontal gyrus in response to increased working memory load. Conclusions: These preliminary findings support the importance of IL‐6 and CRP in brain function among older adults. Frontal and parietal regions may be particularly sensitive to the effects of inflammation. Additionally, these findings provide preliminary evidence of inflammatory contributions to level of neural activity, even after accounting for vascular risk factors.